THE IMAGE OF THE BORDER GUARD IN SOCIETY - Zariņa, Dace; Arbidāne, Iluta; Znotiņa, Daina (Border Security and Management, 2023)
The profession of border guard is one of the oldest professions and plays an important role in the functioning of the state. Its image is shaped by public perceptions of the professional activities, behaviors and attitudes of its members. In principle, it is a set of opinions about the reputation, prestige and popularity of the profession. In order to find out and study the public opinion on the image and prestige of the border guard profession in today's changing conditions, the authors of the article both discusses theoretical findings on the image of the profession and, by analyzing the results of a survey, studies the public opinions on the image of the border guard profession. The public values professionalism, the highest human values (honesty, justice, patriotism, loyalty, etc.), kind and responsive communication, visual image, as well as positive publicity about the sector, achievements of border guards and other positive events.